Perbandingan Kualitas Rumput Odot (Pennisetum Purpureum Cv. Mott) dan Rumput Pakchong (Pennisetum Purpureum Cv. Thailand) terhadap Performa Sapi Bali di Cv. Rnb Farm Gorontalo - Kadek Yadnyano; Widiastuti Ardiansyah; Susan Mokoolang; Dewa Oka Suparwata (Student Scientific Creativity Journal, 2026)
High-quality forage selection is a central factor in improving Bali cattle performance, particularly in smallholder systems that rely heavily on local feed resources. This study evaluated the effects of odot grass (Pennisetum purpureum cv. Mott) and pakchong grass (Pennisetum purpureum cv. Thailand) on feed intake, average daily gain, and feed conversion ratio of male Bali cattle. The experiment was conducted for 30 days from February to March 2026 at CV. RnB Farm, Gorontalo Regency. Nine male Bali cattle with relatively homogeneous initial body weights of 150–200 kg was assigned to a completely randomized design with three treatments and three replications. The treatments were P0, field grass as the control; P1, 100% odot grass plus concentrate; and P2, 100% pakchong grass plus concentrate. Dry matter intake did not differ significantly among treatments, with values of 6.47 ± 0.19, 6.52 ± 0.19, and 6.55 ± 0.16 kg/head/day for P0, P1, and P2, respectively. In contrast, average daily gain differed significantly, with the highest value observed in P2 at 0.56 ± 0.08 kg/head/day, followed by P1 at 0.52 ± 0.09 kg/head/day and P0 at 0.45 ± 0.06 kg/head/day. Feed conversion ratio also differed significantly, with the most efficient value recorded in P2 at 11.98 ± 2.10. These findings indicate that pakchong grass combined with concentrate provides the best feed efficiency and growth performance, while odot grass remains a promising alternative forage for improving Bali cattle productivity.